2020
DOI: 10.1155/2020/5393058
|View full text |Cite
|
Sign up to set email alerts
|

Gait Recognition Based on the Feature Extraction of Gabor Filter and Linear Discriminant Analysis and Improved Local Coupled Extreme Learning Machine

Abstract: A gait energy image contains much gait information, which is one of the most effective means to recognize gait characteristics. The accuracy of gait recognition is greatly affected by covariates, such as the viewing angle, occlusion of clothing, and walking speed. Gait features differ somewhat by angles. Therefore, how to improve the recognition accuracy of a cross-view gait is a challenging task. This study proposes a new gait recognition algorithm structure. A Gabor filter is used to extract gait features fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…With the advancement of measurement technology and recognition algorithms, support vector machine (SVM), linear discriminant analysis (LDA), and extreme learning machine (ELM) are widely utilized for pattern recognition [25][26][27][28]. Wang et al [29] identified multiple gait patterns and compared the classification performance of SVM and neural networks.…”
Section: Introductionmentioning
confidence: 99%
“…With the advancement of measurement technology and recognition algorithms, support vector machine (SVM), linear discriminant analysis (LDA), and extreme learning machine (ELM) are widely utilized for pattern recognition [25][26][27][28]. Wang et al [29] identified multiple gait patterns and compared the classification performance of SVM and neural networks.…”
Section: Introductionmentioning
confidence: 99%
“…Gait recognition methods [3] can be categorized as model-free (appearance-based) [2,[4][5][6][7][8][9][10][11][12] and model-based [13][14][15][16][17][18][19][20][21][22]. Most gait recognition studies are based on model-free approaches that employ the whole motion pattern of the human body.…”
Section: Introductionmentioning
confidence: 99%
“…It is also worth noting that most of them can only achieve correct results from a specific point of view, usually side view [4,5,[7][8][9]16]. The recent research on model-free methods has focused on eliminating these drawbacks [6,[10][11][12]. Model-based methods infer gait signature directly by modeling the underlying kinematics of human motion.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations